2019
DOI: 10.1016/j.ajodo.2018.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of plaque removal and motivation between a manual toothbrush and an interactive power toothbrush in adolescents with fixed orthodontic appliances: A single-center, examiner-blind randomized controlled trial

Abstract: Introduction: The objective of this 2-arm parallel trial was to determine the plaque removal efficacy (main outcome) and the motivation assessment (secondary outcome) comparing a manual versus an interactive power toothbrush in orthodontic patients. Methods: Sixty adolescents with fixed orthodontic appliances in both arches were randomized in a 1:1 ratio in this parallel, randomized, examiner-blind controlled clinical trial. Eligibility criteria included at least 16 natural teeth, 1-6 "focus care areas," plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
(36 reference statements)
0
25
0
1
Order By: Relevance
“…In addition, research among specific populations, such as studies done with earlier O‐R models among orthodontic patients and implant patients 33‐35 , would provide additional insights to the plaque removal efficacy and gingival health benefits of the toothbrush when compared to use of control brushes. Finally, the role of interactive features with use of the novel O‐R electric toothbrush will be evaluated in future research to understand if they provide improvements in brushing behavior seen with other interactive O‐R toothbrushes 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research among specific populations, such as studies done with earlier O‐R models among orthodontic patients and implant patients 33‐35 , would provide additional insights to the plaque removal efficacy and gingival health benefits of the toothbrush when compared to use of control brushes. Finally, the role of interactive features with use of the novel O‐R electric toothbrush will be evaluated in future research to understand if they provide improvements in brushing behavior seen with other interactive O‐R toothbrushes 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Interactive features have also been introduced to share real‐time feedback to the user, initially via a wireless display and more recently using a Smartphone with app, by communicating information such as brushing force, time, and thoroughness. Research has demonstrated these features generate increased patient compliance and improved brushing habits 10‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…Inevitably, placement of a fixed orthodontic appliance creates plaque retention areas that make cleaning difficult [31]. However, the constant presence of bacterial plaque is inevitably accompanied by numerous undesirable effects such as gingivitis, gingival overgrowth, demineralization of enamel (leading to precarious leucomas and even to caries) and, possibly in extreme cases, attachment loss [32], [33].…”
Section: Discussionmentioning
confidence: 99%